AN IN-DEPTH EXPLORATION OF WORD FORMATION: STRUCTURAL PECULIARITIES OF LEXICON AND TYPES OF ROOT AND AFFIXAL MORPHEMES - Abduraxmanova Zilola Yoqubjon qizi; O’ktamova Mushtariy Sodiq qizi (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Annotation: This scholarly article delves into the intricate realm of word formation, offering a comprehensive examination of the structural nuances inherent in lexicon construction. The exploration centers on the fundamental components of word creation, scrutinizing the diverse types of root and affixal morphemes that play pivotal roles in shaping linguistic expressions. The study not only elucidates the inherent complexities of morphological processes but also sheds light on the interplay between these structural elements, unraveling the intricate tapestry of language evolution. By thoroughly dissecting the various types of morphemes, the article elucidates the mechanisms through which words derive their meanings and undergo semantic transformations. Through meticulous analysis, the authors provide insights into the dynamic interrelationships among root morphemes, prefixes, suffixes, and infixes, contributing to a nuanced understanding of the lexicon's rich structure. Furthermore, the article explores the implications of these structural peculiarities on language acquisition, semantic shifts, and cross-linguistic variations. The interdisciplinary approach adopted in this study bridges the gap between linguistic theory and practical applications, offering valuable insights for educators, linguists, and language enthusiasts alike.